ANATOMIC VARIABILITY OF THE PANCREAS ORGANOMETRIC TRANSFORMATIONS IN HUMAN FETUSES AND NEWBORNS - Slobodian, O.M.; Hrymailo, N.A.; Lukyantseva, H.V.; Lukashiv, T.O. (World of Medicine and Biology, 2020)
Pancreas studies were performed on 72 samples of human fetal corpses (from 4 to 10 months) with the mean parieto-calcaneal length of 165.0 to 500.0 mm and on 9 samples of newborns by means of morphological examination. It is established that in fetal and early neonatal ontogenetic periods the typical pancreas shape is curved (72±5 %) and its alternative forms are arched (18±4 %) and straight (10±2 %). The organometric pancreatic parameters and its anatomic parts have two periods of the accelerated development and one period of the relatively slow development. The second period of the relatively slow development is defined only for the gland body width. The model of predicting the standard values of pancreatic morphometric parameters has the following design: pancreatic length = β0 + 0.094 x parieto-calcaneal length of a human fetal corpse, where β0: 3.342 if the age period = 4 months; 4.731 = 5 months; 6.924 = 6 months; 10.349 = 7 months; 8.244 = 8 months; 13.821 = 9 months; 17.489 = 10 months; 18.087 = newborns.
Keywords: pancreas; anatomy; fetus; newborn; human